Overview of plasma-tungsten surfaces interactions on the divertor test sector in WEST during the C3 and C4 campaigns - M. Diez; M. Balden; S. Brezinsek; Y. Corre; N. Fedorczak; M. Firdaouss; E. Fortuna; J. Gaspar; J.P. Gunn; A. Hakola; T. Loarer; C. Martin; et al. (Nuclear Materials and Energy, 2023)
Studying the ageing of tungsten monoblocks, their erosion and their fuel inventory is the priority of the WEST post-mortem analyses programme. Actively-cooled ITER-like plasma-facing units (PFUs) and special W-coated marker lower divertor tiles were retrieved from the WEST divertor after the C3 and C4 experimental campaigns to perform ex-situ analyses. The erosion/deposition pattern on the divertor was determined. The deposition is found mainly on the inner side which is covered by layered deposits that increase in thickness in the radial direction from a few hundreds of nm to a maximum of >10 µm. The deposits are mainly composed of W, O, C, B and D coming from transport of W in the vacuum chamber, oxidized layers and boronizations. Traces of Cu, Fe, Mo, Cr, Ag were also detected. A maximum deposition rate of about 1.4 nm/s was estimated while a minimum campaign-averaged net erosion rate of 0.1 nm/s was measured for the erosion markers at the strike line areas. No assessment of the erosion could be done for the W monoblocks due to a lack of diagnostics. However, the W monoblock edges clearly show traces of damage (melting, cracks) when exposed to the parallel heat flux due to relative misalignment of ITER-like PFUs during assembly. Optical hot spots were also evidenced, confirming the numerical simulations, although their impact on the operation and the lifetime of the components was limited.